Multidrug-resistant Staphylococcus hominis subsp. novobiosepticus causing septicemia in patients with malignancy - Priyamvada Roy; Nishat Hussain Ahmed; Indu Biswal; Rajesh Kumar Grover (Wolters Kluwer Medknow Publications, 2014)
A new subspecies of Staphylococcus hominis described by Kloos et al. in 1998 and named S. hominis subsp. novobiosepticus (SHN) has been implicated in nosocomial outbreaks. Multidrug resistance, including resistance to novobiocin and oxacillin, is a particularly important feature of SHN. In our institute, we encountered 13 cases of S. hominis subsp. hominis in cancer patients with septicemia, of which seven were methicillin resistant. The isolates were identified by VITEK ® 2 compact automated system, using GP REF 21342 identification card and antimicrobial susceptibility testing card P-628. The biochemical reactions and antibiotic susceptibility pattern of the seven methicillin-resistant isolates were re-analyzed and patient details were re-checked to finally identify them as SHN. The increasing number of cases reporting isolation of SHN from biological specimens point to potential virulence and clinical importance of this bacterium.